Strategic foresight for multilateral policy: Challenges, opportunities and success factor - Lars Brozus (Stiftung Wissenschaft und Politik (SWP), 2019)
Increasingly, states are openly and assertively pursuing their national interests in international politics. The US, for instance, is revoking important international agreements on disarmament, trade and climate change. Other countries with a claim to global power, such as China and Russia, are pursuing an aggressive territorial policy. The withdrawal of the UK from the European Union (EU) would mean the loss of an important partner, undermining its ability to implement a strategic and self-confident course of action at the international level. This is all the more worrying since any erosion of the rules-based international order requires a forward-looking and effective policy for shaping the future. Every time a binding international agreement is called into question or revoked, the threshold for uncoordinated unilateral action is lowered. Unexpected crises and conflicts might therefore occur more frequently in the future. Consequently, governments wanting to promote multilateralism should invest in joint strategic foresight. A multiperspective approach appears to be promising for identifying situations in which coordinated action with like-minded partners offers opportunities to proactively shape international affairs.
Keywords: 320